Multiple foreign body granulomas after mastectomy with intraoperative application of tissue adhesive vs. surgical drainage – sonographic finding - Alwafai, Zaher; Lenz, Franziska; Kohlmann, Thomas; Flieger, Carolin; Reichert, Verena; Rutkowski, Julia; Zygmunt, Marek; Ohlinger, Ralf (Ultraschall in der Medizin - European Journal of Ultrasound, 2024)
Purpose The use of tissue adhesive instead of a drain following mastectomy was a point of interest for many breast surgeons. Postoperative formation of multiple unusual sonographic lesions was observed in patients that underwent mastectomy with TissuGlu. The aim of this study was to describe the sonographic features of these lesions and, when possible, to examine them histologically.Materials and Methods This study includes 98 patients, 49 underwent mastectomy with the application of TissuGlu and 49 with drain insertion. Unusual postoperative sonographic findings were thoroughly described. A histological examination was carried out according to the guideline recommendations.Results Unusual sonographic findings were detected in 87.8% of patients in the TissuGlu group and in only 4% of the patients in the drain group. These lesions were detectable between 6 and 59 months postoperatively. 47 breasts of the TissuGlu group were classified as category 3, while only 2 breasts as category 4. Lesions were on average 7.5 mm in diameter, echogenic or isoechoic with posterior shadowing, an irregular and ill circumscribed marginal contour, and a horizontal axis. All histologically examined lesions (n=29) were benign. Granulomatous tissue was histologically proven in 63% of those lesions (n=17), while residual adhesive material could be detected in 18.5% of lesions (n=5).Conclusion The use of TissuGlu adhesive after mastectomy may cause the formation of unusual palpable granulomas, with or without residual adhesive materials. Sonographic description of lesions will help physicians to differentiate between granulomas and local relapse.
Keywords: local recurrence; tissue adhesive; Tissuglu; AREAS, STRUCTURES & SYSTEMS; breast; granuloma